2019
DOI: 10.1177/2049463719857099
|View full text |Cite
|
Sign up to set email alerts
|

‘All these things don’t take the pain away but they do help you to accept it’: making the case for compassion-focused therapy in the management of persistent pain

Abstract: Background: People with persistent pain are frequently offered a pain management programme (PMP) as part of their care plan. Cognitive behavioural therapy (CBT) principles often underpin PMPs and has a good evidence base; nevertheless, more recent systematic reviews have suggested that its effectiveness is limited. Compassion-focused therapy (CFT) is a form of ‘third-wave CBT’ that offers an alternative and complementary view of pain, encouraging the person to be alongside their experience of pain and respond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Evidence-based psychological theories and treatments to manage chronic pain (CP) have shifted from 'first-wave' behavioural approaches (Fordyce, 1976) to 'secondwave' cognitive-behavioural approaches (McCracken & Turk, 2002) and then to 'third-wave' -mindfulness, compassion (Gooding et al, 2020;Kabat-Zinn et al, 1986) and contextual-behavioural approaches (Hayes et al, 2006;McCraken, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence-based psychological theories and treatments to manage chronic pain (CP) have shifted from 'first-wave' behavioural approaches (Fordyce, 1976) to 'secondwave' cognitive-behavioural approaches (McCracken & Turk, 2002) and then to 'third-wave' -mindfulness, compassion (Gooding et al, 2020;Kabat-Zinn et al, 1986) and contextual-behavioural approaches (Hayes et al, 2006;McCraken, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies suggested that ACT interventions also promote self-compassion ( Yadavaia et al, 2014 ; Luoma and Platt, 2015 ), a non-judgmental and mindful approach to one’s pain and suffering ( Neff, 2003 ), which presents known links with pain regulation systems, such as heart-rate variability ( Rockliff et al, 2008 ), and oxytocin-endorphin systems ( Rockliff et al, 2011 ). Self-compassion has been the focus of growing attention in CP due to its protective role against depressive symptomatology in this condition ( Carvalho et al, 2019 ), its negative association with pain disability ( Wren et al, 2016 ), and the promising results showing the positive effects of compassion-based interventions in CP ( Chapin et al, 2014 ; Ziemer et al, 2015 ; Parry and Malpus, 2017 ; Gooding et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acceptance and commitment therapy is a behavioural therapy focused on developing psychological flexibility through a range of strategies, while mindfulness‐based interventions focus on: developing a relationship with experience characterised by present moment focus; decentring and an approach orientation; and support the development of qualities such as compassion, wisdom and greater self‐regulation. Additionally, compassion focused therapy, originally developed with the purpose of treating depression with high levels of shame, may be particularly helpful for those with persisting pain which is compounded by a significant psychological component [53].…”
Section: Managementmentioning
confidence: 99%